2018
DOI: 10.3390/medicines5030066
|View full text |Cite
|
Sign up to set email alerts
|

Use of References in Responses from Scandinavian Drug Information Centres

Abstract: Background: The aim of this study was to compare use of references in responses from Scandinavian drug information centres (DICs). Methods: Six different fictitious drug-related queries were sent to each of seven Scandinavian DICs. The six queries concerned adverse effects, pharmacokinetics, pregnancy, complementary medicine, polypharmacy, and breast feeding. References in the responses were categorised into five types of drug information sources: primary (original studies), secondary (reviews), tertiary (drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…We studied the use of references in the answers from 2013 and compared it to the results from a 1993 study in a Scandinavian DIC s etting. 19 In agreement with previous findings, 3 tertiary literature s ources seem to be useful for most types of questions. Original a rticles were especially useful in questions concerning drug use in | 491 COMMENTARY pregnancy and breast-feeding.…”
Section: Commentsupporting
confidence: 87%
See 2 more Smart Citations
“…We studied the use of references in the answers from 2013 and compared it to the results from a 1993 study in a Scandinavian DIC s etting. 19 In agreement with previous findings, 3 tertiary literature s ources seem to be useful for most types of questions. Original a rticles were especially useful in questions concerning drug use in | 491 COMMENTARY pregnancy and breast-feeding.…”
Section: Commentsupporting
confidence: 87%
“…

n ot imply that the more time one spends processing a question, t he poorer the answer. 19 In agreement with previous findings, 3 tertiary literature s ources seem to be useful for most types of questions. The answers with the lowe st quality were quite easy to identify, whereas high-quality answers were more difficult to point out, as the differences between scores of individual responses were small.

…”
supporting
confidence: 88%
See 1 more Smart Citation
“…A study done by Schjott et al 14 also reported that the studied DICs utilized tertiary reference to answer drug queries in 124 (50.8%) instances. 14 Behera et al 3 reported that websites were commonly used references for answering drug query received by them. As our study centre is a medical college with undergraduate (MBBS) and postgraduate (MD / MS) programs, easy accessibility to textbooks and preference of faculties for answers from textbooks could have led to higher utilization of textbooks for DI.…”
Section: Discussionmentioning
confidence: 99%
“…The study from Scandinavia also reported that only one type of source of information is not sufficient. 14 Gitanjali et al reported that drug advertisements published in Indian and British editions of the British Medical Journal also contained inadequate scientific information. 19 Tertiary sources of DI like the European summaries of product characteristics were also reported to be deficient by several studies as information related to prescribing medicines in special situations was inadequate.…”
Section: Discussionmentioning
confidence: 99%